Do comment letters from the stock exchanges have governance effect on R&D manipulation? - Youfu Yao; Shuang Xue; Tong Sun (China Journal of Accounting Studies (CJAS), 2020)
As an important reform of supervision, the comment letter mechanism adopted by the Shanghai Stock Exchange and the Shenzhen Stock Exchange has been paid much attention by regulators and academics. Taking Chinese A-share listed firms from 2015 to 2018 as our samples, this paper investigates the impact of comment letters on companies' R&D manipulation. Our empirical results show that R&D-related comment letters can effectively reduce companies' R&D manipulation. Further tests show that the more timely the comment letters and responses letters, or the stronger the intensity of comment letters, the higher the governance effect of comment letters on R&D manipulations. Specifically, when R&D-related comment letters involve the questions of R&D manipulation directly, the governance effect is pronounced. The governance effect of R&D-related comment letters is stronger for firms which are punished following the receipt of comment letters or firms which are paid more market attention. Finally, from the perspective of motivations of R&D manipulation, the governance effect of R&D-related comment letters is more pronounced in samples with strong tax-reducing incentives. After employing PSM-DID to control endogeneity, the main results are still held. To sum up, our findings enrich the growing body of research on the effectiveness of the comment letter mechanism and provide important implications for improving the resources allocation in R&D.
Keywords: 650; Front-line supervision; R&D-related comment letters; R&D manipulation; timeliness of comment letters; tax-reducing incentives